Molecular analysis of effects of Andrographis paniculata (Hempedu bumi) on oxidative stress enzymes and lipase in Staphylococcus aureus - Abd Razak, Zayan Nabilah Rasyidah (2017)
A.paniculata leaves are known to have antimicrobial activities and is widely used in traditional medicine worldwide. This study investigated the anti-oxidative properties of methanolic leaves extract of A.paniculata (0.06 mg/ml, MIC) against S.aureus (ATCC 25923) (3.8 x 108 cfu/ml) by determining the ability of the extract to reduce toxicity of hydrogen peroxide (H2O2) against S.aureus. Effects of the extract on gene expressions were determined by RT-qPCR and corresponding activity assays of catalase (katA), superoxide dismutases (sodA and sodM), alkylhydroperoxide reductase C (ahpC) and lipase (geh) in S.aureus were also perfomed. For hydrogen peroxide (H₂O₂) sensitivity test, S.aureus cells (3.8 x 108cfu/ml) were challenged separately with 7.5 mM H2O2 only, 7.5 mM H₂O₂ and methanolic leaves extract of A.paniculata (0.06 mg/ml) and methanolic leaves extract of A.paniculata (0.06 mg/ml) only. Cells challenged with H₂O₂ only showed 0% survival in 30 minutes whereas 25% cells survived after treatment with the extract and H2O2. S.aureus cells that were treated with extract only had 43% survival in the same exposure period. Nitroblue tetrazolium (NBT) reduction assay was performed to determine intracellular and extracellular levels of O₂- after treatment with the extract. Extract –treated S.aureus cells had significantly lower intra- and extracellular O₂- levels with absorbance readings (A575nm) of 0.340 and 0.524 respectively compared to untreated cells which were 0.516 and 0.928 respectively (P<0.05).